2020
DOI: 10.1021/acs.estlett.0c00177
|View full text |Cite
|
Sign up to set email alerts
|

Fresh versus Photo-recalcitrant Secondary Organic Aerosol: Effects of Organic Mixtures on Aqueous Photodegradation of 4-Nitrophenol

Abstract: In the atmosphere, brown carbon (BrC) molecules can contribute to photochemistry and to the warming and evaporation of cloud droplets. The lifetimes of BrC molecules in these cloud droplets are not well constrained, especially considering the droplets can contain mixtures of organic and inorganic molecules. Here we investigated the kinetics of photodegradation for a representative brown carbon molecule, 4-nitrophenol (4NP), in aqueous solutions at low pH. Three different solutions were compared: one containing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 47 publications
1
24
0
Order By: Relevance
“…The oligomerization of tryptophan were also observed in synthetic cloud water (Bianco et al, 2016a). For the N-and S-containing organics, photochemistry may also cause the release of inorganic nitrate and sulfate (Braman et al, 2020;Laskin et al, 2015;Bruggemann et al, 2020). The main radicals in the atmosphere at night is NO3•, which can form from the gas-phase reaction between NO2 and O3 and enter into cloud droplets.…”
Section: Introductionmentioning
confidence: 92%
“…The oligomerization of tryptophan were also observed in synthetic cloud water (Bianco et al, 2016a). For the N-and S-containing organics, photochemistry may also cause the release of inorganic nitrate and sulfate (Braman et al, 2020;Laskin et al, 2015;Bruggemann et al, 2020). The main radicals in the atmosphere at night is NO3•, which can form from the gas-phase reaction between NO2 and O3 and enter into cloud droplets.…”
Section: Introductionmentioning
confidence: 92%
“…12 ). However, a fraction of SOA appears not to be degraded by UV radiation [ 366 , 368 , 369 ], with the overall effect of the UV radiation depending on the chemical composition of the many different aerosols present in the atmosphere. No attempt has yet been made to quantify the sensitivity of the lifetimes of different SOA to changes in UV radiation as would occur with changes in stratospheric ozone.…”
Section: Air Qualitymentioning
confidence: 99%
“…Zawadowicz et al (2020) measured a higher photolysis rate constant for SOA generated from some precursors (up to 2% of the NO 2 photolysis) as compared to the Hodzic et al (2016) rate constant of 0.04%. However, previous studies also showed that a fraction of SOA does not photolyze (Braman et al, 2020;O'Brien & Kroll, 2019;Zawadowicz et al, 2020); for example, 20% of α-pinene and β-caryophyllene SOA, as well as 10% of isoprene SOA, were measured to be nonphotolabile in their environmental chamber measurements. In addition to wet removal and photolytic loss, recent studies suggest that the heterogenous reactions of gas-phase oxidants (i.e., ozone and hydroxyl radical) with SOA could be additional sinks of SOA (Hu et al, 2016;.…”
Section: 1029/2020ms002266mentioning
confidence: 96%